PENGEMBANGAN MODEL PEMBELAJARAN RECIPROCAL TEACHING PAIR SHARE (RTPS) UNTUK MENINGKATKAN HASIL BELAJAR MIKROBOLOGI MAHASISWA IKIP BUDI UTOMO - Purwaning Budi Lestari; Diyah Ayu Widyaningrum (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2016)
The quality of education in Indonesia needs to be improved, One of the efforts undertaken by the college through learning model development. The purpose of this research is to analyze the development of the learning model Reciprocal Teaching Pair Share (rtPS) in improving student learning outcomes microbiology and Testing the effectiveness of the learning model Reciprocal Teaching Pair Share (rtPS) in improving student learning outcomes at the Teachers' Training College Budi Utomo. The model used in this research is the development model of Thiagarajan 4D (1974). The 4D model has four stages, namely define, design, develop, and disseminate. Design test for individual testing and small scale trial is descriptive, whereas for large-scale field trials using quasi-experimental. Data were analyzed using General Linear Model (GLM) - Multivariate SPSS 16. The results showed that the development model of reciprocal teaching decent pair share used in learning activities. The results of large-scale trial could be concluded no effect on the learning model of cognitive learning outcomes of students. besides the development of a model reciprocal teaching pair share effective in improving student learning outcomes microbiology Budi Utomo Malang Teachers' Training College.Keywords: Learning Outcomes , rtPS ( Reciprocal Teaching Pair Share )